ANALISIS KEPUASAN NASABAH DALAM KUALITAS PELAYANAN JASA PADA PT. BANK RAKYAT INDONESIA (PERSERO) CABANG MARTAPURA UNIT RATU ELOK - Rizki Amalia Afriana; Marpuah - (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2016)
Abstract, Problem this research is unsatisfaction customer to the service ofPT. Bank Rakyat Indonesia (Persero) Cabang Martapura Unit Ratu Elok. The population and sample are 100 customer of PT.Bank RakyatIndonesia (Persero) Cabang Martapura Unit Ratu Elok. The result of this research show the service is already good and almostsatisfy the customer but still there is a problem such as the teller quantity is notenough, there is no place for customer to complaint and there is no informationif the system is broken. Based on the respond/answer that questioned to thecustomer, the variable that have good result is reliability, on the contrary thevariable that have bad result is tangibles. The bank should pay more attentionto the complaint of the customer and immedietly do everything to fix it, so thecustomer will not disappointed anymore with the service and the facility